Genome‐wide association study identifies an early onset pancreatic cancer risk locus. Issue 8 (1st May 2020) - Campa, Daniele; Gentiluomo, Manuel; Obazee, Ofure; Ballerini, Alba; Vodickova, Ludmila; Hegyi, Péter; Soucek, Pavel; Brenner, Hermann; Milanetto, Anna Caterina; Landi, Stefano; Gao, Xin; Bozzato, Dania; et al.
Abstract: Early onset pancreatic cancer (EOPC) is a rare disease with a very high mortality rate. Almost nothing is known on the genetic susceptibility of EOPC, therefore, we performed a genome‐wide association study (GWAS) to identify novel genetic variants specific for patients diagnosed with pancreatic ductal adenocarcinoma (PDAC) at younger ages. In the first phase, conducted on 821 cases with age of onset ≤60 years, of whom 198 with age of onset ≤50, and 3227 controls from PanScan I‐II, we observed four SNPs (rs7155613, rs2328991, rs4891017 and rs12610094) showing an association with EOPC risk ( P < 1 × 10 −4 ). We replicated these SNPs in the PANcreatic Disease ReseArch (PANDoRA) consortium and used additional in silico data from PanScan III and PanC4. Among these four variants rs2328991 was significant in an independent set of 855 cases with age of onset ≤60 years, of whom 265 with age of onset ≤50, and 4142 controls from the PANDoRA consortium while in the in silico data, we observed no statistically significant association. However, the resulting meta‐analysis supported the association ( P = 1.15 × 10 −4 ). In conclusion, we propose a novel variant rs2328991 to be involved in EOPC risk. Even though it was not possible to find a mechanistic link between the variant and the function, the association is supported by a solid statistical significance obtained in the largest study on EOPC genetics present so far in the literature. Abstract : What's new? Early‐onset pancreatic cancer (EOPC), diagnosed between ages 45 and 60, accounts for about one‐fifth of all pancreatic cancers. Nonetheless, while multiple epidemiological risk factors for EOPC have been identified, very little is known about genetic susceptibility. The present genome‐wide association study identifies four novel single nucleotide polymorphisms specific for patients diagnosed with pancreatic cancer at younger ages. Among the variants, 13q22.3_rs2328991 was associated with elevated risk in an independent set of pancreatic cancer patients, some of whom experienced disease onset at age 50 or younger. The findings highlight a need for further research on the genetics of EOPC.